Demythologizing the myth of Peter Pan a semiotic analysis of myths in selected Philippine children's literature - Calaunan, Jesica May (2014)
This study utilizes Roland Barthes concepts of Semiotics and Mythologies to analyze selected contemporary Philippine children's short stories. It also includes J.M. Barrie's Peter Pan and Dr. Dan Kiley's Peter Pan Syndrome as its frameworks in studying the selected texts.
In this study, the myth of Peter Pan is considered as one of the myths related to childhood. Thus, this research is directed towards discovering whether the myth of Peter Pan is present even in the Philippine context of children's literature. Through an initial structural analysis, the myth of Peter Pan is evaluated in the texts. A semiotic analysis of dominant signs in the texts follows to draw out myths in the stories. Apart from the myth of Peter Pan, the study is able to draw out other myths in the texts such as the myth of Beauty, Acceptance, Valuable, Obedience, and Punishment. These myths are found to be recurring in the selected texts.
In conclusion, the study found out that Philippine children's stories do not only reinforce mythologies in texts but also counter-reinforce them. Moreover, the research also discovered that the countering of the myth of Peter Pan in the texts also leads to the countering of other myths present in the stories -- Author's abstract.
Thesis (Bachelor of Arts Language and Literature) -- University of the Philippines Baguio, 2014.
Includes bibliographical references.
Keywords: Barrie, J. M. -- 1860-1937. -- History and criticism; Myth in literature; Peter Pan (Fictitious character) -- Adaptations; Children's literature, Philippine -- History and criticism; Children's stories, Philippine -- History and criticism